Innovations and Challenges in Global Air Cargo Logistics - Setiadi (Logistica : Journal of Logistic and Transportation, 2025)
Air cargo logistics has become a critical enabler of global trade and e-commerce, requiring rapid adaptation to technological innovation and evolving regulatory environments. This study examines how efficiency, technological advancement, and regulation interact to shape the future of the sector. A systematic narrative review was conducted using Scopus, Web of Science, and Google Scholar, applying targeted keywords and rigorous inclusion criteria. Findings reveal that efficiency improvements are strongly linked to optimization algorithms and automation, which reduce costs and handling times. Emerging technologies such as drones, digital twins, and artificial intelligence expand logistical capabilities by enabling real-time monitoring, predictive analytics, and improved accessibility. Regulatory frameworks established by the FAA, EASA, and IATA exert decisive influence on adoption, underscoring the importance of adaptive and harmonized policies. Sustainability and resilience also emerge as central, with green logistics initiatives and pandemic responses demonstrating the interdependence of efficiency, environmental responsibility, and systemic adaptability. This review highlights that the trajectory of global air cargo logistics will depend on policies that balance innovation with sustainability and safety.